Interaction between Bacteroidetes species in the fermentation of Lycium barbarum arabinogalactan. (30th May 2023) - Cao, Cui; Wang, Lilong; Zhang, Xueqian; Ai, Chunqing; Wang, Zhongfu; Huang, Linjuan; Song, Shuang; Zhu, Beiwei
Graphical abstract: Highlights: Lycium barbarum arabinogalactan (LBP-3) can be utilized by Bacteroidetes species. Of 10 tested species, P. vulgatus and B. caccae are more powerful to utilize LBP-3. P. vulgatus and B. caccae preferred to Ara and Gal residues in LBP-3, respectively. Oligosaccharides generated by P. vulgatus and B. caccae were identified by LC-MS n . Their fermentation products with mono/oligo-saccharides influence others' growths. Abstract: The present study investigated the utilization of an arabinogalactan from Lycium barbarum (LBP-3) by intestinal Bacteroidetes species. The mixed-culture assay showed 58.4 % LBP-3 was utilized, and Bacteroides caccae and Phocaeicola vulgatus utilized more LBP-3 in single-culture compared to others. During in vitro fermentation of LBP-3, P. vulgatus favored arabinose while B. caccae preferred galactose. Moreover, 9 and 25 oligosaccharides were identified by HPLC-MS n in conditioned media (CM) derived from B. caccae and P. vulgatus, respectively. All of 3 tested Parabacteroides species ( P. distasonis, P. goldsteinii, and P. johnsonii ) markedly proliferated in CM of B. caccae and P. vulgatus, and proliferations of B. uniformis, B. finegoldii, B. ovatus and B. thetaiotaomicron also increased significantly in CM of B. caccae. The study suggests that the ability of Bacteroidetes species to degrade LBP-3 and sheds light on cooperative interactions of Bacteroides, Phocaeicola, and Parabacteroides species in the presence of LBP-3.